Sleep hygiene in adolescents with asthma. (2nd January 2020) - Lawless, Casey; Turner, Elise M.; LeFave, Elizabeth; Koinis-Mitchell, Daphne; Fedele, David A.
Abstract: Objective: Youth with asthma are at-risk for sleep difficulties due to nocturnal asthma symptoms. Sleep hygiene, or the ability to practice consistent sleep behaviors and habits, impacts youth sleep quality and may, as a result, influence daytime cognitive functioning. The current study sought to examine the impact sleep hygiene has on sleep quality, health-related quality of life (HRQL) and sustained attention among adolescents with asthma. It was hypothesized that worse sleep hygiene would be associated with poorer sleep quality, lower school-related and overall HRQL and worse sustained attention. Methods: Participants included 41 adolescents with persistent asthma ( M age  = 14.83, SD = 1.28; 51.2% male) recruited from a pediatric pulmonology clinic. Participants completed the adolescent sleep hygiene scale (ASHS), Adolescent Sleep Wake Scale (ASWS) and the Pediatric Quality of Life Index 4.0 generic core scales (PedsQL). Participants also completed the psychomotor vigilance task (PVT), an objective test of sustained attention. Results: Higher sleep hygiene scores were related to higher reported sleep quality ( β  = 0.377, p  = 0.015, f 2  = 0.166), higher reported school-related HRQL ( β  = 0.321, p  = 0.040, f 2  = 0.115) and better sustained attention ( β  = 0.327, p  = 0.045, f 2 = 0.120). Conclusions: Sleep hygiene may be an important factor in sleep quality and deficits in daytime dysfunction including sustained attention and school-related quality of life. As adolescents with asthma are at heightened risk for these outcomes associated with disturbed sleep, sleep hygiene may serve as an important domain for clinical intervention.